Schistosoma mansoni Worm Infection Regulates the Intestinal Microbiota and Susceptibility to Colitis. - Floudas, Achilleas; Aviello, Gabriella; Schwartz, Christian; Jeffery, Ian B.; O'Toole, Paul W.; Fallon, Padraic G. (Infection and Immunity, 2019)
worm infection modulates the host's immune system and suppresses bystander colitis while limiting dysbiosis of the host's intestinal microbiome during infection.